The role of the industrial cluster strategy In achieving the competitiveness of small and medium industries - LAKHLEF, Athmane (Dirassat Journal Economic Issue, 2012)
Industrial cluster’s strategy is one of the most important tools to develop small and medium industries and to support their productivity; it helps them to achieve many competitive features; it also helps them to use new technologies, and reduce productive costs in addition to increase the quality and final products’ competitiveness. Small and medium size industries occupy a great importance in advanced and developing countries. They participate in stimulating growth strategies for the purpose of jobs creation, diminishing poverty and redistributing income, all these preoccupy a priority in the elaboration of economic policies. In counterpart, these industries encounter many problems refer mainly to the small size and high costs. According to some last studies, these problems do not only depend on the size but also on their dissociation and on imperfect structures. Industrial cluster has been appeared as a tool to support small and medium industries in local and foreign markets. This tool provides several features, it helps increasing specialization and labor division; it leads to reduce exchange costs during the phase of production and therefore reducing costs which allows them increasing their competitiveness